Performance analysis of solar-wind-diesel hybrid standalone renewable energy systems suitable for Malaysian climate / Sk. Shezan Arefin - Sk. Shezan , Arefin (2016)
A large number of populations of the world live in rural or remote areas those are geographically isolated. Power supply and uninterrupted fuel transportation to produce electrical power for these areas poses a great challenge. Using renewable energy in off grid hybrid energy system might be a pathway to solve this problem. Malaysia is a hilly land with the gift of renewable energy resources such as solar energy, wind energy, wave energy, tidal energy, biomass etc. There is a possibility to utilize these renewable resources to produce electrical power and to limit the dependency on the fossil fuel. In this perspective, a research is carried out to analyze the performance of three different hybrid renewable energy systems suitable for different territories of Malaysia. Three different hybrid renewable energy systems are off-grid PV-diesel hybrid energy system, off-grid wind-diesel hybrid energy system and off-grid PV-wind-diesel-battery hybrid energy system. The performance analysis of the three different energy systems have been conducted for southern region of Malaysia, Cameron highlands of Malaysia and a remote area named Kuala Lumpur International Airport Sepang station in the state of Selangor, Malaysia. Real time field data of solar radiation and wind speed are used for the simulation and optimization of operations using “HOMER” renewable energy software. The analyzed system can assure the reduction of CO2 emission in about 16 tons per year in comparison with other energy system. The analyzed hybrid energy system might be applicable for other region of the world where the climate conditions are similar. The electrification process of the remote areas and decentralized areas are being a vital fact for the improvement of its agricultural, eco-tourism and industrial issues of various territories of Malaysia. Renewable energy resources can be used extensively to fulfil the demand of expected loads of these areas. This dissertation presents an analysis of an off-grid PV-diesel, wind-diesel and a PV-wind-diesel energy system. The main objective of the present analysis is to visualize the optimum volume of systems capable of fulfilling the requirements of expected loads for a decentralized area of the region. From the analysis it is observed that according to the cost of energy (COE) or per unit cost and the load demand for the three different conditions three representative energy systems has been developed as follows southern region (PV enriched area), Cameron highland (wind enriched) and the KILA Sepang station (solar and wind both enriched) and the COE sequentially USD 0.895/kWh, USD 0.199/kWh and USD 1.877/kWh. The load demand had been considered sequentially 38, 85 and 33kWh/d for the three different territories of Malaysia as follows southern region (PV enriched area), Cameron highland (wind enriched) and the KILA Sepang station (solar and wind both enriched). The main theme of this analysis is to minimize the electricity unit cost and ensure the most reliable and feasible system to fulfil the requirements of the desired or expected energy system using HOMER software. The decrement of the CO2 emissions also can be identified from the simulation results (with experimental data collected from Malaysian Meteorological department) by using that most feasible renewable energy system.